2011
DOI: 10.1248/bpb.34.1690
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gap Junction Modulators on the Rhythmic Contractions in Aortas Isolated from Rats Subjected with Sinoaortic Denervation

Abstract: The sinoaortic denervation (SAD) is a proceeding that interrupts the arterial baroreceptor reflex system. The hemodynamic alterations produced by SAD have been extensively studied in many mammals, including rats. There is general agreement that SAD causes a substantial increase in arterial pressure lability with no changes in the mean level of blood pressure.1-3) Therefore, SAD rats can be used to study physiological changes caused by high arterial pressure lability without sustained hypertension. There are fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Cx37, Cx40, Cx43, Cx45, and Cx46 are the main Cxs in the cardiovascular system (23,31). It has been shown that the functional abnormalities of gap junctions are related to several cardiovascular diseases, such as atherosclerosis, hypertension, and arrhythmias (44,37). Angelillo-Scherrer et al (5a) reported that deletion of Cx37 in mice shortened the bleeding time and increased thrombus propensity, thus providing a mechanism by which Cx37 limits thrombus propensity by downregulating platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Cx37, Cx40, Cx43, Cx45, and Cx46 are the main Cxs in the cardiovascular system (23,31). It has been shown that the functional abnormalities of gap junctions are related to several cardiovascular diseases, such as atherosclerosis, hypertension, and arrhythmias (44,37). Angelillo-Scherrer et al (5a) reported that deletion of Cx37 in mice shortened the bleeding time and increased thrombus propensity, thus providing a mechanism by which Cx37 limits thrombus propensity by downregulating platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%